Morphological features of tweeks and nighttime D region ionosphere at tweek reflection height from the observations in the low-latitude Indian sector - Maurya, A.K.; Singh, Rajesh; Veenadhari, B.; Kumar, Sushil; Cohen, M.B.; Selvakumaran, R.; Pant, P.; Singh, A.K.; Siingh, D.; Inan, U.S. (My University, 2012)
A total of 19,308 tweeks recorded during April 2007 to March 2008, at Allahabad, a low-latitude station in the Indian sector, has been used to study seasonal occurrence which shows maximum tweek occurrence of about 63% during summer season and about 19% and 18% occurrences during equinox and winter seasons. Maximum occurrence of tweeks during summer season is consistent with the larger number of lightnings detected by World Wide Lightning Location Network in the Indian and Asia Oceania regions during summer as compared to that during equinox and winter. Seasonally, tweek (ionospheric) reflection height in the premidnight (18:00-00:00 LT) during winter is less as compared to that during equinox and summer. Annual (seasonal average) variation of the mean ionospheric reflection height shows a gradual increase in the reflection height from about 19:30 to 04:30 LT. The annual average of postmidnight (00:00–06:00 LT) reflection height is about 5 km higher as compared to that in the premidnight. Our initial results on the variability in the ionospheric reflection height under pure nighttime propagation (21:00–03:00 LT) on magnetically quiet days show a day-to-day variability of up to 8 km. Theoretically calculated attenuation of the Earth-ionosphere waveguide for first six tweek modes in the early and late night periods (21:00–00:00 LT; 00:00–03:00 LT) is less compared to that in the dusk (18:00–21:00 LT) period. The higher attenuation in the dusk period and most of the tweeks in the dawn period traveling partially under daytime conditions explain the lower occurrence of tweeks in these periods.
Keywords: Low-latitude station; Ionosphere; Allahabad; D-region